Experimental study on low-strength concrete joint core strengthened with steel meshes for connecting PFCC column and RC beam. Issue 4 (March 2021) - Yu, Feng; Feng, Chaochao; Fang, Yuan; Liu, Qiqi; Hu, Yi; Bu, Shuangshuang
This paper presented a new joint core strengthened with multi-layer steel meshes for connecting the PVC-FRP Confined Concrete (PFCC) column and Reinforce Concrete (RC) beam. Seven specimens were tested under concentric compression and the effects of several parameters including the height, diameter of specimen and volume ratio of steel mesh on the compressive behaviors were investigated. Test results showed that all the reinforcement yielded successively and eventually the crushing of the concrete dominated the failures of specimens. The ultimate bearing capacity and ultimate equivalent axial strain decreased as the height of specimen increased, while they increased as the diameter of specimen or the volume ratio of steel mesh increased. The ultimate strains of all the reinforcement and concrete increased as the height of specimen increased while they decreased as the diameter of specimen or the volume ratio of steel mesh increased. Considering the influence of height of specimen, a modified formula for conveniently predicting the ultimate bearing capacity of the joint core strengthened with steel meshes was proposed based on the theory of confined concrete and superposition principle of multiple confinement. The predicted results were in good agreement with the experimental data. Additionally, an equivalent stress–strain relationship model of the joint core strengthened with steel meshes was suggested based on the experimental research. The predicted curves agreed well with the measured equivalent stress–strain curves. Moreover, a validated Finite Element (FE) model for the joint core strengthened with steel meshes was developed to conduct parametric studies, which broadened the available experimental results about the mechanical performances of the joint.